Estudios sobre plantas andinas, vi (1945)
Diplostephium subincisum Cuatr., sp. nov. / Diplostephium cinerascens Cuatr., sp, nov. / Diplostephium floribundum subsp. farallonense Cuatr. nova. / Diplostephium violaceum Cuatr., var. puracense Cuatr. nova. / Aphanactis cocuyensis Cuatr., sp. nov. / Liabum tabanense Cuatr., sp. nov. / Steiractinia aspera Cuatr., sp. nov. / Brunellia latifolia Cuatr . sp. nov. / Brunellia occidentalis Cuatr., sp.. nov. / Brunellia Trianae Cuatr., sp. nov. / Pinguicula diversifolia Cuatr., sp, nov. / Pinguicula huilensis Cuatr., sp. nov. / Hedyosmum toxicum Cuatr., sp. nov. / Hedyosmum Granizo Cuatr., sp. nov. / Hedyosmum crassifolium Cuatr. sp. nov. / Hedyosmum llanorum Cuatr., sp. nov. / Hedyosmum colombianum Cuatr., sp. nov. / Hedyosmum huilense Cuatr., sp. nov. / Hedyosmum translucidum Cuatr., sp. nov. / Gentiana cocuyana Cuatr., sp. nov.